Marine Plastics Abatement Challenges, Implications, Assessments and Circularity (Volume 1) - Koottatep, Thammarat; Ekbordin Winijkul; Wenchao Xue; Atitaya Panuvatvanich; Visvanathan, Chettiyappan; Pussayanavin, Tatchai; Limphitakphong, Nantamol; polprasert, chongchin (IWA Publishing, 2023)
Marine Plastics Abatement Volume 1 provides comprehensive knowledge of plastic pollutions in marine ecosystems and their implications on human health, especially from the contamination of micro and nano-plastic particles by which the levels of plastic pollutions in marine, aquatic, terrestrial and atmospheric systems are described. In addition to emerging challenges by plastic pollution, this volume offers comprehensive assessment tools as well as practical models on "Circular Economy" with interesting real-world case studies and theoretical and numerical questions and solutions, recent scientific information, and practical exercises, to ensure a user-friendly text for readers.